Calcified Leiomyoma of the Distal Forearm in a Child: A Case Report and Review of Literature - Nadeeke Nidhan Perera; Sunil Ranjith Wijayasinghe; Karuna Dissanayake; Jerard Fernando; Ethige Tharushi De Silva (Case Reports in Orthopedics)
Background. Deep somatic leiomyomas arising in skeletal muscle are extremely rare in children, especially in the extremities. Around half of them show calcifications. We present a rare case of a calcified leiomyoma of the distal forearm in a child. Case Summary. A seven-year-old boy presented with right distal forearm and wrist pain with restricted supination for 4 years. X-ray showed ring and arc calcifications in the distal forearm at the interosseous area. MRI also confirmed a well-defined soft tissue lesion with areas of calcifications. A diagnosis of a cartilage-forming lesion or a peripheral nerve sheath tumour was suggested. The lesion was completely excised. Histology showed a lesion composed of intersecting fascicles of spindle cells with stromal calcification having immunohistochemical features of a leiomyoma. Conclusion. Although soft tissue calcifications can be seen in a plethora of conditions seen in daily orthopaedic practise, a high index of suspicion should be maintained for rare conditions like deep somatic leiomyoma.